V.1 - "Bagchi,K.K. (ed.)" (Delhi, 2008)
The book deals with three very important issues of contemporary concern in India. These are the issues of agrarian crisis, farmers' suicide and livelihood security of rural labour. The issues have been incorporated into two volumes. In Volume I, studies related to agrarian crisis and farmers' suicide have been included, while Volume II incorporates the studies related to the livelihood security of the agrarian and rural labour. As the ongoing farmers' suicides and economic destruction of farmers and rural labourers continues, with intermittent media reports and apathy from ruling quarters, the contributors generally shunned the explanations offered by media and the political parties. They have gone deeper into the causes and tried to analyse the problems with economists' mind. The papers are empirical and exploratory in nature written by both promising young scholars and experienced researchers. It is hoped that the book will be useful to researchers, academicians and policy makers and administrators alike who have an interests in the topics and who are somehow related and concerned with the issues. About Author : Dr. Kanak Kanti Bagchi is currently Professor and Head Department of Economics, University North Bengal, Raja Rammohunpur, Darjeeling, West Bengal, India. He has a wide teaching experience at undergraduate, postgraduate and research levels. He is also supervising research works of students at M Phil and PhD levels. His main fields of interest are Agricultural Economics, Development Economics and Labour Economics. He has published many research articles in various national and international journals and nine books including two textbooks at undergraduate level and seven books as research publications. He has also presented a number of papers at University, state national and international level Workshops, Seminars and Conferences. Contents : Contents Preface & Acknowledgements Contributors
Keywords: Rural labour